Methylmercury, Mn2+ and Pb2+ Exposure Promotes Premature Proliferation/Differentiation of Human Neural Stem Cells in Different Ways - Ying, Wenyan; Qi, Tongbing; Shi, Dongzi; Zhang, Jing; Ye, Ganghui; Tian, Xuewen; Wang, Qinglu (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Methylmercury (MeHg), manganese ions (Mn2+), and lead ions (Pb2+) are ubiquitous environmental pollutants and may be neurotoxic especially during fetal development. We decided to explore the toxic mechanisms of MeHg (organic heavy metals), Mn2+ (inorganic heavy metals) and Mn2+ on the proliferation and differentiation of human neural stem cells (hNSCs). Materials and Methods: The proliferation and apoptosis of hNSCs were analyzed via CCK-8 method and flow cytometry under MeHg, Mn2+ and Pb2+, respectively. RNA-seq was used for analyzing proliferation/differentiation mechanism of MeHg, Mn2+ and Pb2+ stressing hNSCs. Results: Our experiment found that when hNSCs were exposed to below 0.5 nM MeHg, 5μM Mn2+ and 10 μM Pb2+, cell proliferation and differentiation were promoted. Apoptosis rates increased significantly when hNSCS were exposed to exceed 0.5 nM MeHg, 5μM Mn2+ and 10 μM Pb2+. RNA-seq results showed that metal ions altered the genes expression level and signaling pathways of hNSC differentiation and proliferation, but the regulatory mechanisms of MeHg, Mn2+ and Pb2+ were different. Conclusion: Our findings indicated that very low-dose metal exposure may deplete hNSC pool by making prematurely differentiated neurons increase, which may be the real cause of long-term nervous system disruption in adulthood, rather than higher metal doses will cause more direct toxicity during infant development.
Keywords: Methylmercury; Manganese ion; Lead ion; Neural stem cells; Cell differentiation